Modified Limberg flap technique for sacrococcygeal pilonidal sinus: a retrospective analysis - Zhao Shen; Yang Xiaoyuan; Lin Wanlin; Ma Qiaoling; Zhu Jiandong; Zhang Lei; Yang Limin; Chen Wenping (结直肠肛门外科)
[Objectives] To analyze the clinical effect of modified Limberg flap technique for sacrococcygeal pilonidal sinus. [Methods] Fifty-four patients with sacrococcygeal pilonidal sinus treated with modified Limberg flap technique between August 2015 and November 2021 were included. Depending on the different technique of the modified Limberg flap technique, patients were divided into three groups: offset midline group (n=18), apex angle blunting group (n=20), and conformal flap group (n=16). The indices related to surgery (extubation time, suture removal time), postoperative complications (subcutaneous effusion, incision dehysis, incision infection), cure rate, and recurrence of the three groups were recorded and compared. [Results] All patients underwent successful surgery. The extubation time of the offset midline line group was significantly shorter than that of the apex angle blunting group and conformal flap group (P<0.05). There was no significant difference in the suture removal time among the three groups (P>0.05). In the offset midline group, 5 patients had subcutaneous effusion, 6 patients had incision dehysis, and 3 patients had incision infection; in the apex angle blunting group, 1 patient had subcutaneous effusion, 2 patients had incision dehysis, and 1 patient had incision infection; in the conformal flap group, no patients had subcutaneous effusion, incision dehysis, and incision infection. Eighteen were cured in the offset midline group, 19 in the apex angle blunting group and 16 in the conformal flap group. Patients were followed up until September 2022 with a median of 42 (18, 56) months. No patients were lost to follow-up. During the follow-up, only one patient in the apex angle blunting group experienced recurrence, while no recurrence was reported in the other two groups. [Conclusion] Compared with the offset midline technique and the apex angle blunting technique, conformal flap technique as a new type of modified Limberg flap technique for treating sacrococcygeal pilonidal sinus shows comparable effectiveness while reducing the incidence of postoperative subcutaneous effusion, incision dehysis and incision infection.